A literatura infantil como prática de letramento através da oralidade - Farias, Angelica Torres Vilar de (2014)
Reading is a theme frequently discussed in researches and in the academic environment. We intend with the present research, to analyze and reflect about the reading of infant literature which text are written as recreations of the oral textual genre that Cascudo (1984, p. 329) classifies as Cumulative Tale, in which refers to its approach, in the intention of literacy, in classes from fundamental teaching I. Specifically we intent to research about the oral expression and oral genres present in books of infant and juvenile literature founded at MEC libraries in public schools from Taperoá. We consider making a survey of books which texts would be ‗inspired or that revisited the thematic or the forms of oral expression of popular culture. We aimed to point representations of oral expression (explicit of implicit) in the texts chosen for analysis. This choice conducted the research to the analysis of these books, in the sense of support a pedagogical work, in the classroom, in order to increase the student s literacy process. It was observed, among other aspects referent to the oral expression in the classroom, that the mediation of reading realized by the teacher, with reading activities, will collaborate to these results. In this study, we are based in assumptions of Kleiman (1995, 2005, 2012), Geraldi (1996, 1997, 2001), Soares (2000, 2003, 2004, 2012), Dolz & Schneuwly (2004), Marcuschi (1997, 2001, 2003, 2005, 2010), Ong (1998) and Zumthor (2003, 2010). From a more ample universe of research, we analyzed a selection of four books of infant literature, which texts can be classifies as cumulative tales. The book s analysis provided an amplification of our vision about the importance of the oral expression that can be developed from readings of infant literature, in the literacy process of a subject.